BaCo0·4Fe0·4Zr0·1Y0·1O3–δ triple conductor for boosting electrode efficiency for proton conducting fuel cells. (26th January 2022) - Kim, Chanho; Lee, Hyungjun; Jang, Inyoung; Kim, Sungmin; Jung, Hoyeon; Ryu, Myeungwoo; Kim, Jeongheon; Lee, Dongsoo; Yoon, Heesung; Paik, Ungyu; Song, Taeseup
Abstract: Proton conducting fuel cells (PCFCs) are considered as promising energy generation system due to their possibility for lowering the operation temperature. PCFCs operated at low temperature by conducting small and light protons, which enables stable operation without undesirable side reactions by thermal corrosion. However, kinetic energy for redox reaction at electrodes is insufficient due to the decreased operating temperature, resulting in degraded electrochemical performance. In this study, by forming BaCo0·4 Fe0·4 Zr0·1 Y0·1 O3-δ (BCFZY), a triple conducting material which could conduct proton, oxygen ions, and electrons at the electrodes, the power generation performance of PCFCs has been improved dramatically. BCFZY nanoparticles provide a charge passage, and effectively expand the reaction site. A proton conducting fuel cells with electrodes containing BCFZY exhibit an enhanced power density of 1.06 W cm −2 at 650 °C, which is almost 3 times higher value than the cell without formation of BCFZY on the electrodes. Our study proposes an effective strategy for enhancing the performance PCFCs by facilitating the conduction of charge carriers within the electrodes through applying BCFZY triple conductor. Highlights: The triple conducting material is applied on both electrodes for PCFC. The triple conductor expands reaction region by increasing the passage of charge. PCFCs with BCFZY exhibited significant improvements in power density. Almost 3 times higher power density is shown for the cell with BCFZY. Stable working without any degradation is confirmed for 100 h.